2013
DOI: 10.1123/jab.29.6.790
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Center of Pressure Estimation Errors on 3D Inverse Dynamics Solutions During Gait at Different Velocities

Abstract: The aim of this study was to investigate the effect of errors in the location of the center of pressure (5 and 10 mm) on lower limb joint moment uncertainties at different gait velocities (1.0, 1.5, and 2.0 m/s). Our hypotheses were that the absolute joint moment uncertainties would be gradually reduced from distal to proximal joints and from higher to lower velocities. Joint moments of five healthy young adults were calculated by inverse dynamics using the bottom-up approach, depending on which estimate the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The distance between center of mass (CoM) and center of pressure (CoP) (CoM-CoP) at heel strike plays important role in generating the forward propulsion of the CoM [31]. The CoP acting on the plantar surface of the foot with reference to the lower limb joint center changes the moment arm of the ground reaction force vector, thereby influencing the lower limb joint moments [32][33][34]. Due to the rigid ankle joint of the SACH foot and mechanical knee being in extended position at heel strike, different orientation of the shank (pylon in the prostheses) with the laboratory vertical axis influences the location of the CoP at heel strike [32] thereby influencing the joint moment during stance phase.…”
Section: Introductionmentioning
confidence: 99%
“…The distance between center of mass (CoM) and center of pressure (CoP) (CoM-CoP) at heel strike plays important role in generating the forward propulsion of the CoM [31]. The CoP acting on the plantar surface of the foot with reference to the lower limb joint center changes the moment arm of the ground reaction force vector, thereby influencing the lower limb joint moments [32][33][34]. Due to the rigid ankle joint of the SACH foot and mechanical knee being in extended position at heel strike, different orientation of the shank (pylon in the prostheses) with the laboratory vertical axis influences the location of the CoP at heel strike [32] thereby influencing the joint moment during stance phase.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the present study’s standardized beta coefficients, COP RMSE mostly increased due to increasing belt velocity. In support of this, a linear relationship between COP errors and joint moment uncertainties in addition to increasing joint moment uncertainty with increasing gait velocity has been reported [15]. Increases in AP COP error results in magnitude but not pattern changes in joint moments, with joint moment magnitudes and patterns having an even higher sensitivity in the ML direction [16].…”
Section: Discussionmentioning
confidence: 84%
“…The findings of their study indicated the joint moment magnitudes were more sensitive to the COP change in the ML direction than in the AP direction [18]. Camargo et al further investigated the effect of COP during gait at different velocities and concluded that the absolute peak moment uncertainties decreased from distal to proximal joint and also from the lower to higher gait velocity [13]. In these studies, the researchers suggest that the COP errors should be less than 3 mm on average and less than 5 mm of maximum to prevent remarkable changes of joint moment.…”
Section: Discussionmentioning
confidence: 97%
“…Since the location of the COP affects the estimation of joint kinetics including muscle and joint forces [10][11][12][13], and studies of movements on various deformable terrains continue to increase, this research provides valuable guidelines for when it might be acceptable to neglect the effect of a deformable surface on COP. The effect of surface deformation on determining the COP needs to be evaluated to prevent misrepresentation of the results of joint biomechanics of gait on deformable surfaces.…”
Section: Introductionmentioning
confidence: 99%